Antimicrobial Resistance and Antibiotic Consumption in a Secondary Care Hospital in Mexico - Elda Carolina Dávila-López; María Guadalupe Berumen-Lechuga; Carlos José Molina-Pérez; Rodolfo Norberto Jimenez-Juarez; Alfredo Leaños-Miranda; Natali Robles-Ordoñez; María Isabel Peña-Cano; German Alberto Venegas-Esquivel (MDPI AG, 2024)
Background: Antimicrobial resistance is a global health problem, due to morbidity, mortality, and healthcare costs. The misuse of antimicrobials is the main cause of antimicrobial resistance. The aim of this study was to report antimicrobial resistance and antibiotic consumption in a secondary care hospital in Mexico. Methods: Within a cross-sectional study, antimicrobial resistance data on ESKAPE pathogens (Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter species) and antibiotic consumption from 2020 to 2022 were collected. Antimicrobial resistance was reported based on percentages of resistance and consumption was analyzed using the defined daily dose (DDD)/100 bed days and the AWaRe (Access, Surveillance, Reservation) antibiotic group. Results: Antibiotic consumption in 2020, 2021 and 2022 was 330, 175 and 175 DDD/100 beds day, respectively. The rate of ceftriaxone resistance in E. coli (n = 526) and K. pneumoniae (n = 80) was 76% and 69%, respectively, the rate of carbapenem resistance in A. baumannii (n = 168) and P. aeruginosa (n = 108) was 92% and 52%, respectively; the rate of oxacillin resistance in S. aureus (n = 208) was 27%; and the rate of vancomycin resistance in E. faecium (n = 68) was 47%. Conclusion: The reported results are congruent with global estimates of antibiotic resistance and consumption, providing an overview that could generate actions for antimicrobial optimization at the local and regional levels.